Molecular structure and the role of high‐temperature requirement protein 1 in skeletal disorders and cancers. (22nd December 2019) - Li, Yihe; Yuan, Jinbo; Rothzerg, Emel; Wu, Xinghuo; Xu, Huazi; Zhu, Sipin; Xu, Jiake
Abstract: Human high‐temperature requirement protein 1 (HTRA1) is a member of serine proteases and consists of four well‐defined domains—an IGFBP domain, a Kazal domain, a protease domain and a PDZ domain. HTRA1 is a secretory protein and also present intracellularly and associated with microtubules. HTRA1 regulates a broad range of physiological processes via its proteolytic activity. This review examines the role of HTRA1 in bone biology, osteoarthritis, intervertebral disc (IVD) degeneration and tumorigenesis. HTRA1 mediates diverse pathological processes via a variety of signalling pathways, such as TGF‐β and NF‐κB. The expression of HTRA1 is increased in arthritis and IVD degeneration, suggesting that HTRA1 protein is attributed to cartilage degeneration and disease progression. Emerging evidence also suggests that HTRA1 has a role in tumorigenesis. Further understanding the mechanisms by which HTRA1 displays as an extrinsic and intrinsic regulator in a cell type–specific manner will be important for the development of HTRA1 as a therapeutic target.